Gayo Didong Culture as a Foundation for Developing Civic Character in the Younger Generation - Matang Matang; Siti Jannatun Aliyah; Aqshal Arlian Raya; Abdul Rahmad; Syahputra Perdana Astina; Nopri Abadi Miko (Indonesian Journal of Civic and Law Studies (IJCL), 2026)
This study aims to analyze the role of Gayo Didong local culture as a foundation for developing the civic character of the younger generation. Didong is an oral art form of the Gayo community that not only serves as entertainment but also conveys moral, religious, and social values while shaping identity and self-concept. This study employed a systematic literature review by analyzing 48 scientific articles published between 2020 and 2025. The findings indicate that most studies utilized qualitative and literature review approaches focusing on the exploration of values, social meanings, and cultural functions in character development. Didong embodies noble values such as honesty, deliberation, mutual cooperation, social responsibility, and religiosity, which align with the principles of civic education. The integration of Didong cultural values into formal and non-formal education is considered effective in enhancing nationalism, social solidarity, and civic awareness among students. In the era of globalization, Didong also functions as a moral shield and cultural identity that helps the younger generation navigate modernization without losing their identity.